The Instrumentality and Influence of Billboard Political Campaign on Voting Behavior in Nigeria Politics Critical Assessment of Impact - Samson Olukayode Bamidele (Eastasouth Institute, 2026)
The study evaluates the impact of billboard political campaigns on voting behavior in Nigeria, especially during 2019 governorship election in Ekiti State. The study seeks to understand how visual political advertisement influences voters/perceptions, decision-making process, and electoral choice. The study analyses primary data against the background of the objective. Evidences available indicate that billboard advertising significantly shaped voters’ awareness and attitudes towards candidates, serving as a major source of political information and make reinforcement, also that strategic placement, message clarity and visual appeal of billboards positively influenced voter recall and candidate preference. It was equally revealed in the study that excessive commercialization of billboard space and message repetition sometimes led to voter apathy and skepticism, it was concluded in the study that billboard campaigns remain an effective and viable medium of political communication, especially in urban and semi-urban areas, where visibility and accessibility enhance message impact. Therefore, the study recommends that political actors adopt ethical and assure-based billboard messaging focused on policy substance rather than personality, glorification. Lastly, INEC and other regulatory agencies are urged to monitor outdoor political advertising to ensure compliance with campaign guidelines.